Performance improvement of SHWS by increasing thermal efficiency using insulation materials and optimum position of solar collectors - Ferdous, Jannatul M Shafi; Islam, Md Sanzidul; Shaker, Nabil; Khan, Bonnyamin; Azad, AKM Abdul Malek (© 2012 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2nd International Conference on the Developments in Renewable Energy Technology, ICDRET 2012; Dhaka; Bangladesh; 5 January 2012 through 7 January 2012 [© 2012 Developments in Renewable Energy Technology (ICDRET) ]